Symposium on Catholic Schools and the Changing Global Landscape for Faith-Based Education : An Introduction - Wodon, Quentin (Taylor and Francis, 2019)
Despite the fact that faith-based schools serve tens of millions of students (the estimate for the Catholic Church is at 62 million students enrolled in K12 schools globally in 2016), the role of faith-based schools remains largely ignored in policy discussions. The articles and essays in this symposium aim to inform current debates on the role of faith-based schools, and particularly Catholic schools. The focus on Catholic schools is driven by the fact that they are the largest network of faith-based schools globally. It is clear however that many issues faced by Catholic schools are also faced by other faith-based schools.